Evaluation of mulberry cultivars (Morus spp.) in Western Uganda - Esimu, Joseph; Nagasha, Janet; Ssemugenze, Brian; Walimbwa, Emma; Kasiime, Godfrey; Lukoye Kutosi, Demas; Mugisha, Didas; Twikirize, Nipher; Babirye, Sarah; Masiga, Clet Wandui (Journal of Pharmacognosy and Phytochemistry, 2022)
Mulberry (Genus morus) is an economically important plant used for sericulture, as it is the sole food plant for the domesticated silkworm, Bombyx mori. The genus Morus, which is widely distributed in Asia, Europe, North and South America, and Africa, is cultivated extensively in East, Central and South Asia for silk production. Attempts have been made to characterise the genetic diversity in mulberry. This experiment was set up in a randomized complete block design with three replications for each variety. Ten agronomic traits to include Plant Height (HT), Internode Distance, (ID), number of branches per plant, Lamina Length (LL), lamina width (LW), leaf area, leaf yield/plant were studied, data was analyzed statistically using R version 4.0.1 (R Core Team, 2014) and significant differences were considered at P< 0.05. There were significant variations in ten agronomic traits among the tested mulberry accessions. Genetic background and environment are the main factors influencing leaf yield. Correlation matrix of different traits showed that leaf yield is a combination of multiple traits and plays a significant role. Leaf yield per plant significantly differed across all the varieties but branching varieties such as S.36 recorded highest leaf yield compared to other varieties studied.
Keywords: Diversity; Mulberry; Cultivar; Morphology; Accession; Sericulture